Long-Term Preoperative Nonsteroidal Anti-inflammatory Drug Use Does Not Impact Revision Rate After Repair of Rotator Cuff, Achilles, Distal Biceps, or Quadriceps Tendon - Romir Parmar, B.S.; Sailesh V. Tummala, M.D.; Alejandro Holle, B.S.; Jose Iturregui, M.D.; Alexander J. Hoffer, M.D.; John M. Tokish, M.D. (Arthroscopy, Sports Medicine, and Rehabilitation)
Purpose: To determine whether long-term preoperative nonsteroidal anti-inflammatory drug (NSAID) use affected the revision rates after primary tendon repair for the following common sports medicine surgical procedures: rotator cuff repair (RCR), Achilles tendon repair (ATR), distal biceps repair (DBR), or quadriceps tendon repair (QTR). Methods: A retrospective comparative study using a national insurance database was performed. Patients who underwent major tendon repair, including RCR, ATR, DBR, or QTR, with at least 2-year follow-up were identified. Those who had a diagnosis of long-term NSAID use prior to the index operation were identified and matched 1:4 to controls without NSAID use based on age, sex, specific tendon repaired, and Elixhauser Comorbidity Index. The revision repair rates of the 2 groups were compared. Results: A total of 36,068 patients underwent major tendon repair. Of these, 7,246 (20%) met the long-term NSAID use criteria prior to tendon repair (NSAID users). After RCR, 3.2% of NSAID users (n = 190) and 2.6% of controls (n = 617) underwent revision surgery within 2 years (odds ratio [OR], 1.15; 95% confidence interval [CI], 0.97-1.36; P = .10). After ATR, NSAID users had a revision rate of 3.9% (n = 24) versus 2.5% (n = 62) in the control cohort (OR, 1.47; 95% CI, 0.89-2.38; P = .12). After DBR, both NSAID users and controls had fewer than 11 revision cases (OR, 1.54; 95% CI, 0.49-4.16; P = .42). After QTR, the revision rate was 5.9% (n = 30) for NSAID users compared with 4.8% (n = 95) for the control group (OR, 1.22; 95% CI, 0.77-1.86; P = .38). None of the observed differences in revision rates between NSAID users and controls were significant. Conclusions: Patients with a diagnosis of and coding for long-term preoperative NSAID use do not have greater revision rates within 2 years of primary tendon repair than patients without this diagnosis. Level of Evidence: Level III, retrospective case-control study.